The Effect of Aerobic and Parallel Exercise Methods on Selected Hematological Variables and Heart Function in Patients Aged 40 to 65 Years Following Coronary Angioplasty - Baghban Baghdadabad , Masoumeh; Sadeghi, Heydar; Matinhomaee, Hassan; Sokhangoii, Yahya (Journal of Clinical Physiotherapy Research, 2020)
Introduction: Considering the important role of cardiac rehabilitation exercises for patients after coronary angioplasty, this study aimed to determine the effect of an eight-week parallel exercise period on hematological variables (red and white blood cells, hemoglobin, and hematocrit) and cardiac function (functional capacity, ejection fraction, and maximum oxygen consumption) in patients aged 40 to 65 years following the coronary angioplasty. Materials and Methods: In this semi-experimental study with pre-and post-test design, 90 men and women with coronary heart disease who underwent angioplasty, were randomly divided into two experimental groups (aerobic and parallel exercise) and a control group. Using the instructions of ACSM, 40 minutes of aerobic exercise in eight weeks for rehabilitate of heart patients (three times a week) in the aerobic exercise group, and 40 minutes of aerobic exercise (three times a week) and 20 minutes of resistance exercise program (twice a week) in parallel exercise group. The control group had no exercise other than the recommendation of three days of walking during the week. Kruskal-Wallis and Mann-Whitney U tests were implemented to compare pairs of groups in variables with abnormal distribution. In normal variables, the Levin test was used to check the homogeneity of variance of the data. Due to heterogeneity of variance, the Welch test and Tamhane's T2 Post-Hoc test were used for intra- and inter group comparisons at a significance level of 0.05. Results: Using parallel exercise, selected hematologic variables (hemoglobin and red blood cells) were significantly increased. Also, selected variables of cardiac function including (maximum oxygen consumption and ejection fraction and functional capacity) through aerobic and parallel exercises in middle-aged patients following coronary angioplasty, showed an increasing trend. The variable of maximum oxygen consumption in the parallel exercise group was significantly higher than the aerobic exercise group. Conclusion: According to findings, the beneficial effects of both regular aerobic and parallel exercises in appropriate intensity and duration with the priority of parallel exercise are recommended to improve hematological variables and cardiac function in patients 40 to 65 years after coronary angioplasty.